Comparison of stress distribution in dental crown with different cusp angles: 3D finite element analysis. Issue 3 (17th February 2019) - Kim, Han-Wool; Choi, Byung-Ho; Bae, Eun-Jeong; Lim, Joong-Yeon
Abstract: The purpose of this study is to measure the failure risk of a crown depending on the cusp angle. Three all-ceramic crown models consisting of CH (high incline), CM (middle incline), and CL (low incline) are designed. Stress is applied to the crown with Loading case-1 (top of cusp tip) and Loading case-2 (middle of cusp ridge) with the use of FEA software. In Loading case-1 and case-2, the CH showed the highest Maximum Principal Stress (MPS) while the CL showed the lowest MPS. The cusp angle is an influential factor affecting stress distribution in dental crowns.